"Sometimes I Wish I Was a Girl, 'Cause They Do Shit Like Cry": An Exploration Into Black Boys' Thinking About Emotions. (February 2022) - Harris, Johari; Kruger, Ann C.; Scott, Edward
Social-emotional learning (SEL) is important for academic and social success, yet responsive SEL for Black youth remains underexamined. The current study analyzed focus groups to investigate how Black boys ( N = 10) in an urban middle school think about emotion and its regulation. Results revealed that participants negotiate tension between emotion expression and control; they argued that inhibition of emotions in public was essential, but they desired greater emotional freedom. We interpret these patterns through the developmental framework of accommodation and resistance. We discuss implications and the need for transformative SEL in urban schools serving Black boys.